Urban mindscapes of Europe - Weiss-Sussex, Godela; Bianchini, Franco, 1959- (European studies (Amsterdam, Netherlands) ;, 2006)
Urban mindscapes are structures of thinking about a city, built on conceptualisations of the city's physical landscape as well as on its image as transported through cultural representation, memory and imagination. This book pursues three main strands of inquiry in its exploration of these 'landscapes of the mind' in a European context. The first strand concerns the theory and methodology of researching urban mindscapes and urban 'imaginaries'. The second strand investigates some of the representations, symbols and collective images that feed into our understanding of European cities. It discu.